SARS-CoV-2 in First Trimester Pregnancy: A Cohort Study. Issue 4 (April 2021) - la Cour Freiesleben, N.; Egerup, P.; Hviid, K. V. R.; Severinsen, E. R.; Kolte, A. M.; Westergaard, D.; Olsen, L. Fich; Prætorius, L.; Zedeler, A.; Christiansen, A.-M. H.; Nielsen, J. R.; Bang, D.; et al.
Abstract : (Abstracted from Hum Reprod 2021;36(1):40–47) Pregnant women are at an increased risk of viral infections and increased risk of serious morbidity such as severe pneumonia, particularly during the first trimester. COVID-19 (coronavirus disease 2019) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).